Análisis de las exigencias técnicas – funcionales del sistema contra incendios y su incidencia en la eficiencia energética, para la subestación eléctrica Celec Ep de 60 mw de la empresa CSED S.A, en la ciudad de Quinindé, provincia de esmeraldas, durante el año 2015. Propuesta para el diseño, simulación y construcción de un sistema contra incendios mediante criterios de eficiencia energética. - Díaz Chicaiza, Eduardo Javier (2016)
Fires in electrical substations are a latent threat, being the most devastating as they involve energized electrical equipment, electrical failure can cause a fire, accompanied by heavy losses of assets and productivity, damage to the substation staff and service interruptions. At present in our environment, in the design of fire protection systems, there is insufficient integration of the analysis of the technical-functional requirements and the generation of solution variants that are energy-efficient, which has allowed to create the bases to refine the approach of the solution to the problem under study. Therefore, the present study has the aim to analyze the technical requirements-functional anti-fire system and its impact on energy efficiency for the electric substation CELEC EP 60 MW of the company CSED S.A in Quinindé, Province of Esmeraldas, in 2015. During the development of research and the generation of the solution variant, CAD / CAE systems for automated design and the simulation of anti-fire system were implemented and used, and the procedure for risk analysis used was based on the application of Gretener Method. The proposed solution was the design, simulation and construction of an energy efficient anti-fire system. It was determined that the overall efficiency of the pumping network in the anti-fire system is 85.26%, which allows us to obtain an installation according to NFPA, INEN, API, ISO and IEEE standards; this involves the efficient selection of equipment and components of the fire protection system at the Quinindé substation.